1996
DOI: 10.1577/1548-8659(1996)125<0472:sfwdai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Fine Woody Debris Accumulations in a Stream Increase Rainbow Trout Fry Abundance

Abstract: Habitat for young-of-the-year rainbow trout Oncorhynchus mykiss was enhanced in a fourthorder stream during August-October 1991 by the addition of wooden structures that simulated accumulations of fine woody debris (FWD). The experiment represented a two-factorial design with the presence or absence of FWD bundles and time since debris introduction as factors. Immediately after FWD placement, fry density, individual biomass, fry condition factor, and total fry biomass were similar in treated and untreated site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The addition of bundles of small trees enhanced winter habitat within pools for coho salmon through an increase in cover (Nickelson et al 1992) (Table 1). Log deflectors (Näslund 1989), half-log structures (Van Zyll de Jong et al 1997), and structures made of thin wooden louver boards (Culp et al 1996) also provided covers for salmonids and were associated with increased salmonid abundance (Table 1).…”
Section: Wood Installation Measures and Fish Responsesmentioning
confidence: 99%
“…The addition of bundles of small trees enhanced winter habitat within pools for coho salmon through an increase in cover (Nickelson et al 1992) (Table 1). Log deflectors (Näslund 1989), half-log structures (Van Zyll de Jong et al 1997), and structures made of thin wooden louver boards (Culp et al 1996) also provided covers for salmonids and were associated with increased salmonid abundance (Table 1).…”
Section: Wood Installation Measures and Fish Responsesmentioning
confidence: 99%
“…Addition of LWD also created sites where leaf pack and fine woody debris accumulated. Culp et al (1996) found the addition of fine woody debris increased the density of YOY rainbow trout (Oncorhynchus mykis) in a Canadian stream. Also, Nislow et al (1999) showed early season age-0 Atlantic salmon (Salmo salar) preferred slower current velocities associated with areas where LWD and boulders were added in Connecticut River tributaries (VT, U.S.A.).…”
Section: Brook Trout Populationsmentioning
confidence: 99%
“…The addition of woody debris to streams has often enhanced habitat and increased fish populations (e.g., Everett & Ruiz, 1993;Culp et al, 1996;Roni & Quinn, 2001;Zika & Peter, 2002;Shields et al, 2006) and its removal reduced populations (Angermeier & Karr, 1984;Dolloff, 1986;Elliott, 1986;Fausch & Northcote, 1992), although these effects have not always occurred (Spalding et al, 1995;Keith et al, 1998;Warren & Kraft, 2003;Sweka & Hartman, 2006). The basis for these differences in response has not been explained at the population level (Spalding et al, 1995), and been questioned at the community level (Lepori et al, 2005).…”
mentioning
confidence: 99%